Identification Of Metallo?-Lactamses and Integron Genes In Pseudomonas Aeruginosa Isolated From Burn Injury Patients: Phenotype And Genotype - Ashraf Ayyal Mutar Alrashedi (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
Pseudomonas aeruginosa, which generates metallo-?-lactamase (MBL), is the cause of infections linked to burn patients, and this is a growing global problem. The objectives of the recent study were to determine antibiotic susceptibility of P. aeruginosa isolates, the presence of MBLs genes, and Integron gene class-1 . One hundred burn patients at the Al-Hussein Teaching Hospital in Al Smawah, Iraq, were isolated clinically. Twenty (20%) of these were determined to be P. aeruginosa by 16sRNA and biochemical testing. To further identify the antibiotic sensitivity for each isolate was employed by Disc Diffusion Method . The phenotypic MBL production For detected isolates was evaluated by Combined Disc Diffusion Method (CDD). Integron gene class -1 (Int-1) and Genes encoding MBLs were identified by Polymerase Chain Reaction (PCR). P. aeruginosa was shown to be totally resistant to ceftriaxone, ampicillin, piperacillin, gentamicin, and ciprofloxacin in this investigation. 90% of the isolates were determined to be multidrug resistant, and different levels of moderate to lowest resistance were observed in Amikacin, Meropenem, Aztreonam, Cefixime, and Levofloxacin. While 90% of the isolates possessed the Int-1 gene, our recorded the absence of All MBLs genes (Bla IMP, Bla VIM, Bla GIM ) From All isolates under investigation. Illustrating for the first time how crucial it is to put in place appropriate infection control measures in order to give patients the best care possible and stop the development of these resistant microbes among burn patients.